2012
DOI: 10.1177/1461445612452976
|View full text |Cite
|
Sign up to set email alerts
|

‘Gossiping’ as a social action in family therapy: The pseudo-absence and pseudo-presence of children

Abstract: Word count = 7170 excluding references and title page Running head: Gossiping as a social action Acknowledgements = We would like to offer our thanks to Professor Panos Vostanis, Dr Khalid Karim and Claire Bone for their guidance and comments on this paper and extend thanks to the ESRC for funding this project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…This management of the multiple attempts to blame the child for the problems in the family is something that therapists may be aware of from the beginning. This study suggests that blaming the child, sometimes in particularly derogatory ways, for the family problems is fairly typical in these four families and this is something that other research studies have also reported (Asen, , O'Reilly, ; Parker and O'Reilly, ). It may be possible for therapists to anticipate such narratives and begin to deflect such issues from session one.…”
Section: Discussionsupporting
confidence: 72%
“…This management of the multiple attempts to blame the child for the problems in the family is something that therapists may be aware of from the beginning. This study suggests that blaming the child, sometimes in particularly derogatory ways, for the family problems is fairly typical in these four families and this is something that other research studies have also reported (Asen, , O'Reilly, ; Parker and O'Reilly, ). It may be possible for therapists to anticipate such narratives and begin to deflect such issues from session one.…”
Section: Discussionsupporting
confidence: 72%
“…This has been reported as being achieved in two main ways. First, parents can present behavioural examples and dispositional descriptions to emphasise and authenticate the severity of their child’s behaviour (O’Reilly, ; Parker and O’Reilly, ). Second, parents can make direct statements about their own good parenting and appropriate responses to their children’s behaviour (O’Reilly and Lester, ), and family members can emphasise their reliability as informants (Hella et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Therapist responses to blame and maintaining neutrality. Therapists took three main positions in response to blame: alignment, by acknowledging or stating a belief about the blame (Friedlander, Heatherington and Marrs, 2000;Parker and O'Reilly, 2012); disalignment by ignoring and diverting the conversation away from the blame (Friedlander et al, 2000;Pote et al, 2011;Stancombe and White, 2005); or through neutrality by reframing the blaming talk in ways that are consistent with the frame of family therapy. Therapists can reframe talk by focusing on emotions, framing the problem in the context of the relationship, redirecting to talk about resolutions, or using metaphors to expand the theme of the discussion (Friedlander et al, 2000;O'Reilly, 2005b).…”
Section: Therapists' Responses To the Familymentioning
confidence: 99%
“…This type of research has already examined how clinical processes are interactionally constituted in the course of therapy and has explored the role of the therapist in shaping the interaction (Georgaca, 2012). Furthermore, there is increasing recognition that conversational evidence can be useful as a resource for enhancing practice, with the recordings of actual practices offering rich opportunities to see how outcomes are shaped by therapeutic dialogue (Strong, Busch, & Couture, 2008) and for offering practical recommendations for professionals (Parker & O'Reilly, 2012).…”
Section: Using Conversation and Discourse Analytic Research As Evidenmentioning
confidence: 98%